Conformity Level Analysis of Physics Daily Test Questions Based on Minimum Competency Assessment - Luthfiyah Khairi; Desnita Desnita (Postgraduate, University of Mataram, 2023)
This study aims to determine the level of suitability of the daily test questions of physics with Minimum Competency Assessment (MCA) for reading literacy and numeracy literacy at SMA Negeri 1 Kamang Magek class XI MIPA. This research uses quantitative and qualitative descriptive methods with steps for problem analysis, data collection, quantitative analysis in the form of validation and reliability tests, data of grid suitability, analysis of the level of conformity of daily test questions with MCA components, and reports. The data analyzed were obtained from MCA-based daily test questions, grids, and student answer sheets. The data collected was processed using a comparison of MCA aspects that are met with the total number of MCA aspects to find out the percentage of conformity of daily test questions with MCA questions. After analyzing the questions, it is proven that all items are valid. Furthermore, the results of the reliability test made by the teacher showed reliability with some 0.57 basic competencies 3.1 categorized as medium reliability, basic competencies 3.2 medium reliable categories with some 0.57, basic competencies 3.3 medium reliability with some 0.468, basic competencies 3.4 high reliability with some 0.695, and basic competencies 3.5 high reliables with some 0.603. The grids that the teacher made did not yet correspond to the grids that should have been used. The percentage of conformity rate for reading literacy was 58.54%. The percentage of suitability rate for numeracy literacy is 63.67%. Referring to the results of the analysis, it can be concluded that the level of conformity of the questions made by teachers with MCA for reading literacy is categorized as sufficient and the level of suitability of questions made by teachers with MCA for numeracy literacy is categorized as high.